Sekolah Tinggi Penerbangan Riau Dengan Pendekatan Arsitektur Hijau (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Lack of the needs of expert sources in the aviation in Pekanbaru become a problem in the transportation. Provision of flight as air transportation facilities must be supported by the human resources that are reliable and competent in their fields. Flight school become into a facility to produce human resources that are reliable and competent, especially in the field of aviation, both pilots, engineers, and teachers. Air Transportation Institute of Riau is an institute with a vocational level, which is a school that organizes learning by only one profession. In the design of air transportation institute needs to see the proper application of the concept. Green architecture is an appropriate theme for the time being due attention to the impact of the design for the future. Itâs need to consider the application of the theme of green architecture in the design of the air transportation institute. The application of green architecture is based on standards of Green Building Council Indonesia (GBCI). There are 12 mass at the air transportation institute of Riau district which consists of educational building, workshop building, dormitory building, religious building, and service building. The concept is applied to the area of the air transportation institute of Riau that is green connection. Green connection is applied in a way to give more efficient access to open space as a liaison. Air transportation institute of Riau is designed by applying the principles of green architecture that is conserving energy, working with climate, respect for site, respect for user, limiting new resources, and Holistic. Observations were carried out by using solar panels on every education building. Made ponds as a water catchment so that water isnât wasted in vain. Air transportation institute of Riau is made of the existing problems such as noise, lighting, and made efficient circulation in every building.Keywords: Aviation Institute, Green Architecture, GBCI